2004
DOI: 10.1152/ajprenal.00370.2003
|View full text |Cite
|
Sign up to set email alerts
|

The intrarenal renin-angiotensin system in autosomal dominant polycystic kidney disease

Abstract: Hypertension is a common complication of autosomal dominant polycystic kidney disease (ADPKD), often present before the onset of renal failure. A role for the renin-angiotensin system (RAS) has been proposed, but studies of systemic RAS have failed to show a correlation between plasma renin activity and blood pressure in ADPKD. Ectopic renin expression by cyst epithelium was first reported in 1992 (Torres VE, Donovan KA, Sicli G, Holley KE, Thibodeau ST, Carretero OA, Inagami T, McAteer JA, and Johnson CM. Kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
3
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 55 publications
3
97
3
4
Order By: Relevance
“…10 Similarly, the other study showed the existence of RAS components including renin, AGT, ACE, ANG II receptor and ANG II peptide in cysts and in dilated tubules of ADPKD kidneys. 7 In our study, urinary AGT levels tended to be high in ADPKD patients but were not significant statistically. Limited number of subjects may contribute this result.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…10 Similarly, the other study showed the existence of RAS components including renin, AGT, ACE, ANG II receptor and ANG II peptide in cysts and in dilated tubules of ADPKD kidneys. 7 In our study, urinary AGT levels tended to be high in ADPKD patients but were not significant statistically. Limited number of subjects may contribute this result.…”
Section: Discussioncontrasting
confidence: 61%
“…[3][4][5][6][7] Several studies suggest that angiotensinogen (AGT) and the other substances of RAS system are present in autosomal dominant polycystic kidneys. 6,7 These findings implicate that intra-renal RAS may play a main role in ADPKD pathogenesis. Recently, the studies showed UAGT are a useful biomarker to reflect intrarenal RAS activity in some of renal diseases and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in adults with ADPKD have implicated the renin-angiotensin-aldosterone system (RAAS) in the pathogenesis of the hypertension and left ventricular hypertrophy associated with this condition. In this regard, all components of the renin-angiotensin system including angiotensinogen, renin, angiotensin converting enzyme, angiotensin I and II, and angiotensin IA receptor have been identified in adult ADPKD kidneys (14). Circulating plasma renin activity has also been shown to be higher in ADPKD adults as compared with matched patients with essential hypertension in the supine and upright position and after stimulation with the ACE inhibitor captopril (15).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the reduced thapsigargin and CCE responses, PKD cyst cell Ca i 2ϩ elevations in response to angiotensin II and to AVP are of normal magnitude, although slightly delayed in onset. The components of the local renin-angiotensin system are overexpressed in human ADPKD (23), with possible consequences to flow-induced regulation of apical exocytic insertion of AT 1a receptors in proximal tubular cells (16). The prolonged rate of Ca 2ϩ signal decay in PKD cyst cells treated with angiotensin II or vasopressin recalls that produced in ATP-stimulated M1 CCD cells by overexpression of a fusion protein containing the PC1 COOH-terminal cytoplasmic tail (69), attributed by those authors to prolongation of Ca 2ϩ entry.…”
Section: Discussionmentioning
confidence: 99%